2016
DOI: 10.1021/acs.inorgchem.6b00177
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-Directed Fabrication of Four Tetranuclear Quadruple Stranded Helicates Showing Magnetic Refrigeration and Slow Magnetic Relaxation

Abstract: A rare class of four tetranuclear lanthanide based quadruple stranded helicates namely, [Ln4L4(OH)2](OAc)2·xH2O (Ln = Gd(III)(1), Dy(III)(2) and x = 4, 5 respectively), [Er4L4(OH)2](NO3)2·9H2O (3), and [Dy4L4(NO3)](NO3)2·2CH3OH·H2O (4) were synthesized by employing succinohydrazone derived bis-tridentate ligand (H2L) and characterized. Structures of 1-3 are similar to each other except the nature of counterions and number of lattice water molecules. In 4, a distorted nitrate ion was arranged in a hexagonal man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(35 citation statements)
references
References 140 publications
0
35
0
Order By: Relevance
“…From comparative point of view, even though 1 and 2 contain two Dy III centers, their relaxation dynamic behaviors are considerably different. The difference was attributed to the slight changes in the coordination environments around the Dy III centers [19,27,[40][41][42]. This is due to the nature and symmetry of crystal field which controls anisotropy and effects on overall effective energy barrier [43][44][45][46][47].…”
Section: Methodsmentioning
confidence: 99%
“…From comparative point of view, even though 1 and 2 contain two Dy III centers, their relaxation dynamic behaviors are considerably different. The difference was attributed to the slight changes in the coordination environments around the Dy III centers [19,27,[40][41][42]. This is due to the nature and symmetry of crystal field which controls anisotropy and effects on overall effective energy barrier [43][44][45][46][47].…”
Section: Methodsmentioning
confidence: 99%
“…The chain can twist during molecular self‐assembly and offers different binding modes to metal centers. Recently, it has been found that H 4 L 1 can coordinate with Ln III ions and gives rise to helical complexes . Besides, the fact that H 4 L 1 has four labile protons [two –OH and two –C(O)–NH– protons] may also lead to versatile deprotonated states depending on the reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The total length of the helical strand is 13.71 (9) Å with an average pitch of 11.8 Å. [22b] Hydrazine N of [–C(O)NH–] group forms intramolecular H‐bonding (Table S7) with phenolate oxygen from L 2 (N–H ··· O, 2.76 Å). Apart from H‐bonding, C–H ··· π and C–H ··· O interactions support crystal packing arrangements (Figure S2–S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, investigations on the synthesis and explorations of novel coordination compounds with well‐defined properties are a major field of chemical research . A rational design of these arrays implies that the combination of organic components and metal ions has allowed us to access a variety of new material with intriguing architectures and promising applications such as catalysis, luminescence, magnetism, optics, and molecular storage .…”
Section: Introductionmentioning
confidence: 99%